3D eddy current and temperature field analysis of edge induction heater. Issue 2 (7th March 2016) - Li, Yilun; Yang, Shiyou
Abstract : Purpose: – The temperature drop, especially in the edge of rolled steel in the hot rolling cooling has a catastrophic effect on the steel quality. The purpose of this paper is to study the coupled eddy current-temperature field of a C-type edge induction heater to provide references for engineering applications and designs. Design/methodology/approach: – Three-dimensional finite element analysis (FEA) model of a C-type edge induction heater is developed. Especially, a numerical methodology to couple the eddy current and temperature fields is proposed for coupled eddy current and temperature problems involving movement components. FEA software ANSYS is used to solve the coupled eddy current and temperature fields. The heat loss from the eddy current fields is abstracted and processed, and taken as internal heat source in the analysis of the temperature field. The temperature distribution of the rolling steel is obtained. Findings: – The numerical results can predict exactly the temperature rise of the rolled steel by means of the edge induction heating system. Practical implications: – The proposed numerical methodology for coupling eddy current and temperature fields can be applied to engineering coupled eddy current and temperature problems involving movement components. Also, the developed model and method can be used in the analysis and design of the edge induction heating system. Originality/value: – A numerical methodology to couple eddy current and temperature field for solving multi-physics field problems involving movement components is proposed and implemented in available commercial software. A three-dimensional model of the C-type edge induction heat heater is developed. Finite element method is employed to study the coupled eddy current-thermal problem. A method to deal with the movement of the strip steel is proposed. The proposed methodology can be applied to other coupled eddy current-temperature field problem with moving components.